ENVIRONMENT-RESPONSIVE SMART MATERIALS: SUSTAINABLE INNOVATION BASED ON WEST JAVA CLIMATE DATA FOR FUTURE ENERGY TRANSITION - Jogi R. N. Panggabean; Hilmi F. Putra; Irsyad M. Habibie; M. Raihan Hidayat; Julian Kurnia; Kenjiro K. Counedio; Teuku S. Huseen (Multidisiplin Pengabdian Kepada Masyarakat, 2025)
Climate variability demands materials that adapt to environmental changes rather than simply resist them. This study analyzed environment-responsive smart materials for West Java's tropical climate using satellite data (2021-2024) tracking rainfall, sea surface temperature (SST), and chlorophyll-a. Statistical analysis revealed significant correlations: rainfall-SST (r = -0.41), rainfall-chlorophyll-a (r = 0.49), and SST-chlorophyll-a (r = -0.69), creating predictable environmental states affecting material degradation. Metal-Organic Framework (MOF) materials achieved 99% water harvesting efficiency at 80% relative humidity, typical of wet season conditions. Self-healing polymers performed optimally at 29-31°C, matching regional temperatures and minimizing energy requirements. Weathering analysis showed polymers degraded fastest (7.8% annually) versus aluminum (1.7% annually) under wet-dry cycling. Rainfall-optimized circular economy implementation demonstrated 65% resource efficiency improvement and 55% carbon emission reduction compared to traditional systems, with economic value reaching $60 per unit under optimal conditions. Biological recycling achieved 105% efficiency during wet seasons, while chemical recycling performed better during dry periods, suggesting complementary seasonal strategies. Temporal trends indicated precipitation increases and SST decreases consistent with regional climate projections, though natural variability remained dominant. This integrated framework linking satellite climate data with material performance enables evidence-based selection for tropical applications and provides replicable methodology for other regions facing similar environmental challenges.